Thermoregulatory responses and hydration practices in heat-acclimatized adolescents during preseason high school football - Walker Yeargin, S.; Casa, D. J.; Judelson, D. A.; McDermott, B. P.; Ganio, M. S.; Lee, E. C.; Lopez, R. M.; Stearns, R. L.; Anderson, J. M.; Armstrong, L. E.; Kraemer, W. J.; Maresh, C. M. (Journal of Athletic Training, 2010)
Context: Previous researchers have not investigated the thermoregulatory responses to multiple consecutive days of American football in adolescents.